Constraint induced movement therapy in hemiplegic cerebral palsy: a national survey of its use by physiotherapists in the UK - Tucker, Rachael; Drummond, Avril E.R.; Moffatt, Fiona (Mark Allen Healthcare, 2017)
Background/aims: There is an emerging evidence base into the use of Constraint Induced Movement Therapy (CIMT) in hemiplegic Cerebral Palsy (CP). However, there is little evidence of its use in the UK. This study aimed to conduct a national survey of physiotherapists to explore their use of CIMT in hemiplegic CP and to identify barriers and facilitators to its use.